2020
DOI: 10.1016/j.jpedsurg.2019.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical complications after congenital diaphragmatic hernia repair by thoracotomy vs. laparotomy: A bicentric comparison

Abstract: Members of the European Reference Network on Inherited and Congenital Anomalies of the thorax (ERNICA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For infants treated with by laparoscopy the pooled proportion was 0.01 (95% CI 0.01-0.03; n = 7/536; I 2 = 0%; p = 0.00) 18,22,25,26,37,39,40,42,50,51,59,62 . For infants treated by laparotomy the pooled proportion was 0.02 (95% CI 0.01-0.04; n = 26/1098; I 2 = 39%; p = 0.76) 15,17,21,22,28,29,32,33,37,43,45,46,49,52,53,[55][56][57]59,63 . Of the studies that did report on the location of the incision, transverse incision was most reported.…”
Section: Resultsmentioning
confidence: 99%
“…For infants treated with by laparoscopy the pooled proportion was 0.01 (95% CI 0.01-0.03; n = 7/536; I 2 = 0%; p = 0.00) 18,22,25,26,37,39,40,42,50,51,59,62 . For infants treated by laparotomy the pooled proportion was 0.02 (95% CI 0.01-0.04; n = 26/1098; I 2 = 39%; p = 0.76) 15,17,21,22,28,29,32,33,37,43,45,46,49,52,53,[55][56][57]59,63 . Of the studies that did report on the location of the incision, transverse incision was most reported.…”
Section: Resultsmentioning
confidence: 99%
“…2 However, survival may come at the cost of high medium-to long term morbidity rates including chronic lung disease, variable pulmonary hypertension, gastroesophageal reflux, feeding and growth problems, neurocognitive delay, hearing loss, thoracic deformations, and hernia recurrence. [3][4][5][6][7][8][9][10] For parents of children born with CDH, the most relevant long term morbidity may be neurodevelopmental impairment (NDI).…”
Section: Introductionmentioning
confidence: 99%
“…Others are generally related to the severity of the disease, such as prolonged invasive respiratory support, need for intensive care, longer duration of mechanical ventilation, postoperative sildenafil requirement, longer length of stay (LOS), age at discharge, supplemental oxygen requirement, persistent pulmonary hypertension. And others still, like thoracotomy and MIS, are related to surgical choice (12,17,(23)(24)(25).…”
Section: Postnatalmentioning
confidence: 99%